Routine versus selective contrast imaging to identify the need for early re-intervention following laparoscopic fundoplication: A retrospective cohort study. (August 2015) - Shahzad, Khalid; Menon, Ashok; Turner, Paul; Ward, Jeremy; Pursnani, Kishore; Alkhaffaf, Bilal
Abstract: Background: The prompt recognition of complications is essential in reducing morbidity following anti-reflux surgery. Consequently, many centres employ a policy of routine post-operative contrast studies. The study aimed to examine whether routine contrast studies more effectively recognised early post-operative complications following anti-reflux surgery compared with selective use. Methods: This was a retrospective analysis of 240 adults who had undergone primary anti-reflux surgery. Selective use of water-soluble contrast swallows was employed for 115 patients (Group 1) while 125 patients (Group 2) had routine studies. Results: 10 (0.9%) patients from Group 1 underwent contrast studies, four (40%) of which were abnormal. Routine studies in Group 2 identified thirty-two abnormalities (27%) however the inter-group difference was not significant (p = 0.32). Only one case from group 2 required immediate re-intervention. This was not statistically significant (p = 0.78). Multivariate analysis found no significant association between selective or routine imaging and re-intervention rates. One patient from group 2 presented three days following discharge with wrap migration requiring reoperation despite a normal post-operative study. Conclusion: Routine use of contrast imaging following anti-reflux and hiatus hernia surgery is not necessary. It does not identify a significantly greater number of post-operative complications in comparison to selective use. Additionally, routine use of contrast studies does not ensure the diagnosis of all complications in the post-operative period. Highlights: No consensus on contrast imaging following anti-reflux surgery. We compare routine and selective post-operative imaging approaches. We undertake a multi-variate analysis. Post-operative re-intervention rates are low. No support for routine post-operative contrast imaging.